A Literature Review Of 3D Printing In Dental Prosthesis (Journal of Pharmaceutical Negative Results, 2022)
3D printing is a technology of making 3D objects by stacking materials layer by layer, which is also called additive manufacturing process. Today, all clinical aspects, including patient admission, patient records collection and storage, patient diagnostic information acquisition and processing, treatment planning, obtaining data to form three-dimensional images and designing and producing restorations in dentistry, are done with the help of computers. Dental prostheses that are designed and made with the help of a computer (computer-aided design, computer-aided manufacturing) (CAD-CAM) have become popular in recent years. Technology based on CAD-CAM usually includes three stages: 1-data collection or digitization, 2-data processing (CAD), and 3-production (CAM). The purpose of this article is to provide a comprehensive review of the use of 3D printing in the manufacture of dental prostheses. The techniques were studied in terms of the main methods used, materials used, advantages, disadvantages, limitations and applications of each of them in making dental prostheses. Based on the results of this study, 3D printing has a huge transformative capacity in dentistry. Design freedom, mass customization, and the ability to print complex structures with minimal waste of material are the main advantages of 3D printing. Currently, with the help of this cost-effective technology in which the amount of wasted material is very small, casts, special trays, removable prostheses, surgical guides, implants, temporary prostheses, cast patterns, and metal frames can be produced.